WOMEN’S LANGUAGE FEATURES IN MICHELLE OBAMA’S SPEECH “THE FIRST LADY ON THE IMPORTANCE OF STUDYING ABROAD” - Fidelia Ratih Widya Wardani; Maria Kristiani (ELTR Journal, 2017)
The research entitled The Analysis of Women’s Language Features found in Michelle Obama’s Speech “The First Lady on the Importance of Studying Abroad” aims to identify women's language features based on Lakoff theory found in Michelle Obama’s speech. The data were collected using a descriptive qualitative method; the data were gathered by watching the video several times and reading the transcript of Michelle Obama's speech containing the women's language features on Youtube. The data were analysed by using Lakoff (1975) on women's language. The results of this research show that there are 89 items found, 18 items or 20% of lexical hedges or fillers, 1 item or 1% of rising intonation on declaratives, 13 items or 15% of intensifiers, and 57 items or 64% of emphatic stress.